Notary's Responsibility for Violation of Code of Ethics in Signing Authentic Deeds by Sending Minutes of Deeds - Fitrianingtyas, Asma' Fajar; Ma'ruf, Umar (TABELLIUS: Journal of Law, 2025)
This study aims to determine and analyze the actions of Notaries when signing authentic deeds by sending minutes of authentic deeds and to determine and analyze the form of Notary's responsibility for violation of code of ethics in signing authentic deeds by sending minutes of authentic deeds. The results of the research and discussion in this study are: Notaries can sign authentic deeds by sending minutes of authentic deeds because they deviate from the principle of obedience and the Notary's Principle of Prudence towards the code of ethics of 2005 and 2015 Article 4 paragraph (6) of the notary's code of ethics, namely as a strict prohibition on Notaries in sending minutes to clients to be signed. This has an impact on the validity of the deed and the integrity of the notary profession. So that violations of the code of ethics, the Honorary Council will impose sanctions in the form of Reprimands, Warnings, Schorzing (temporary dismissal) from membership of the association, Onzetting (dismissal) from membership of the association, Dishonorable Dismissal from membership of the association and the responsibility of the Notary in sending authentic minutes of deeds has the potential to cause legal uncertainty, where as a form of responsibility the Notary can be subject to administrative, disciplinary, or even criminal sanctions in accordance with the provisions of Law Number 2 of 2014 concerning the Position of Notary. Legal responsibility for the Deed of Sale and Purchase Agreement made by a notary for sending the minutes of the deed to the client even though with the consent of the parties, the Notary can still be burdened with Administrative Sanctions by the Notary Honorary Council in the form of a written warning, so that the notary is responsible for maintaining the credibility of his profession and public trust in him.